The overworked American : - Schor, Juliet B . (HarperCollins, 1991)
This is a book with an important message that unfortunately will probably not be taken seriously. Schor, a Harvard economist, argues from statistics what the rest of us know from experience, that "in the last twenty years the amount of time Americans have spent at their jobs has risen steadily